During the COVID-19 Epidemic: Recommendations for the Admission and Treatment of Patients With Ovarian Cancer - Ling, Yu; Mingxia, Ye; Xiaoyan, Zhang; Yifan, Fan; Peipei, Liu; Yue, Zhang; Yuanguang, Meng; Lian, Li (Frontiers in Surgery, 2021)
Background: The coronavirus disease 2019 (COVID-19) had become a health care event endangering global human. It takes up a large number of healthcare resources. We studied the impact of the COVID-19 on ovarian cancer patients by comprehensively analyzing their admissions before and after the epidemic and made reasonable suggestions to improve the current situation. Methods: We randomly divided enrolled patients into three groups, PreCOVID-19 Group-PCG (2019.8.20 2020.1.20), COVID-19 Group- CG(2020.1.21-2020.6.14),and Secondary Outbreak COVID-19 Group-SOCG (2020.6.15-2020.10.10). One-way ANOVA and chi-square test were used for analysis. Results: The number of patients from other province decreased significantly (p<0.05). The total hospital stay during the epidemic was substantially more extended (p<0.05). Before the epidemic, our department performed more open surgery. While after the epidemic outbreak, we tended to choose laparoscopy (p<0.01). We took longer surgery time (P<0.05). Patients had a significantly less postoperative fever during the epidemic (p<0.001). Conclusion: During the COVID19 epidemic, no patient infected with covid19, and no patient experienced severe postoperative complications. We recommend maintaining admissions of ovarian cancer patients during the epidemic following the rules. 1. The outpatients must complete nucleic acid test and chest CT in the outpatient clinic; 2.Maintain full daily disinfection of the ward and insist that health care workers disinfect their hands after contact with patients; 3.Increase the use of minimally invasive procedures, including laparoscopy and robotics.